Testosterone-induced adult neurosphere growth is mediated by sexually-dimorphic aromatase expression - Ransome, Mark I.; Boon, Wah Chin (Frontiers in Cellular Neuroscience, 2015)
We derived adult neural stem/progenitor cells (NSPCs) from the sub-ventricular zone of male and female mice to examine direct responses to principal sex hormones. In the presence of epidermal growth factor (EGF) and fibroblast growth factor-2 (FGF2) NSPCs of both sexes expressed nestin and sox2 and could be maintained as neurospheres without addition of any sex hormones. The reverse was not observed; neither testosterone (T), 17β-oestradiol (E2) nor progesterone (P4) was able to support neurosphere growth in the absence of EGF and FGF2. 10nM T, E2 or P4 induced nestin(+) cell proliferation within 20 minutes and enhanced neurosphere growth over 7 days irrespective of sex, which was abolished by Erk inhibition with 20M U0126. Maintaining neurospheres with each sex hormone did not affect subsequent neuronal differentiation. However, 10nM T, E2 or P4 added during differentiation increased III tubulin(+) neuron production with E2 being more potent compared to T and P4 in both sexes. Androgen receptor (AR) inhibition with 20M flutamide but not aromatase inhibition with 10M letrozole reduced basal and T-induced neurosphere growth in females, while only concurrent inhibition of AR and aromatase produced the same effect in males. This sex-specific effect was supported by higher aromatase expression in male neurospheres compared to females measured by Western blot and green fluorescent protein reporter. 10M menadione induced oxidative stress, impaired neurosphere growth and up-regulated aromatase expression in both sexes. However, under oxidative stress letrozole significantly exacerbated impaired neurosphere growth in males only. While both E2 and T could prevent oxidative stress-induced growth reduction in both sexes, the effects of T were dependent on innate aromatase activity. We show for the first time that intrinsic androgen and estrogen signalling may impact the capacity of NSPCs to produce neural progenitors under pathological conditions of oxidative stress.